2022
DOI: 10.3390/cells12010026
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte L-Lactate Signaling in the ACC Regulates Visceral Pain Aversive Memory in Rats

Abstract: Pain involves both sensory and affective elements. An aspect of the affective dimension of pain is its sustained unpleasantness, characterized by emotional feelings. Pain results from interactions between memory, attentional, and affective brain circuitry, and it has attracted enormous interest in pain research. However, the brain targets and signaling mechanism involved in pain remain elusive. Using a conditioned place avoidance (CPA) paradigm, we show that colorectal distention (CRD magnitude ≤ 35 mmHg, a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…It is clear that astrocytes play a crucial role in the modulation of neuronal activity and synaptic plasticity. Astrocytes regulate the release of neurotransmitters, and energy substrates such as lactate, 19 , 76 which are considered to be involved in learning and memory. 35 Increasing neuronal activity has been shown to enhance the generation of oligodendrocytes and thickness of individual myelin segments.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that astrocytes play a crucial role in the modulation of neuronal activity and synaptic plasticity. Astrocytes regulate the release of neurotransmitters, and energy substrates such as lactate, 19 , 76 which are considered to be involved in learning and memory. 35 Increasing neuronal activity has been shown to enhance the generation of oligodendrocytes and thickness of individual myelin segments.…”
Section: Introductionmentioning
confidence: 99%
“…Further support was found for an association with others renal function [64]. GFAP levels could reflect neuronal damage in obese of ESRD [65]. GFAP circulating levels have been described in the context of traumatic brain injury [66].…”
Section: Glial Fibrillary Acidic Protein (Gfap)mentioning
confidence: 86%
“…Astrocytes are the main sites of glycogen storage in the CNS, and can rapidly metabolize glycogen to lactate 76 and transport it to neurons during periods of neuronal activity. Recently, we have demonstrated that astrocyte-lactate signalling in the ACC is required in regulating visceral aversive memory 77 .…”
Section: Discussionmentioning
confidence: 99%